1,8,10-Substituted Anthracenes – Hexafunctional Frameworks via Head-to-Tail Photodimerisation - Niermeier, Philipp; Lamm, Jan-Hendrik; Peters, Jan-Hendrik; Neumann, Beate; Stammler, Hans-Georg; Mitzel, Norbert W. (Synthesis, 2019)
Several 1,8,10-functionalised anthracene derivatives and a couple of 1,8,9-functionalised anthracene analogous, bearing alkynyl substituents at positions 1 and 8 were synthesised and their photochemistry investigated in UV irradiation experiments. Almost all compounds could be converted into their 9,10:10′,9′-head-to-tail photodimers completely excluding the formation of the corresponding head-to-head isomers. Working under non-inert conditions led to formation of endoperoxides in some cases. Furthermore, a non-classical [4π+2π] photodimer was obtained from 1,8,10-tris[(trimethylsilyl)ethynyl]anthracene with one of the alkynyl substituents involved in the photoreaction. The 1H and 13C NMR spectra of all classical and non-classical photodimers were compared with those of the endoperoxides identifying characteristic shifts for the atoms at positions 9 and 10. Moreover, solid-state structures were determined for one or more of each representative.
Keywords: anthracenes; photodimerisation; endoperoxides; non-classical photodimers; solid-state structures